1994
DOI: 10.1063/1.357598
|View full text |Cite
|
Sign up to set email alerts
|

Identification of defects and impurities in chemical-vapor-deposited diamond through infrared spectroscopy

Abstract: Hydrogen-, oxygen-, and nitrogen-related defects in chemical-vapor-deposited (CVD) diamond have been observed by infrared spectroscopy and found to affect optical absorptions in spectral regions of commercial interest. The origin of absorptions in the infrared spectrum at 2820 and 2833 cm−1, which have been observed previously without being understood, have been assigned. The presence of these absorptions and the evidence of oxygen and nitrogen incorporation in CVD diamond have important implications for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(46 citation statements)
references
References 15 publications
3
43
0
Order By: Relevance
“…A comprehensive and systematic experimental study of the dependence of incorporated H atom density on processing conditions is not available, but H atom concentrations around 0.5% are commonly measured [22][23][24] in CVD diamond, and up to 1.5% trapped H has been observed [24] in the near sub-surface region. (However, it should be noted that evidence [22][23][24] exists to suggest that much of the incorporated H is located at grain boundaries in polycrystalline diamond.) Since we have not allowed diffusion or outgassing from the film, it is not surprising that the H atom concentrations in Fig.…”
Section: Vacancies and Trapped Hydrogenmentioning
confidence: 99%
“…A comprehensive and systematic experimental study of the dependence of incorporated H atom density on processing conditions is not available, but H atom concentrations around 0.5% are commonly measured [22][23][24] in CVD diamond, and up to 1.5% trapped H has been observed [24] in the near sub-surface region. (However, it should be noted that evidence [22][23][24] exists to suggest that much of the incorporated H is located at grain boundaries in polycrystalline diamond.) Since we have not allowed diffusion or outgassing from the film, it is not surprising that the H atom concentrations in Fig.…”
Section: Vacancies and Trapped Hydrogenmentioning
confidence: 99%
“…The peak at 2820 is related to N center and there are CH stretch vibrations of the C -H bond in the N -CH 3 group. This band has also been assigned to H terminated diamond (111) surface [15]. However, it is observed that the intensity of the band at 2820 cm À 1 increased in the samples deposited with N 2 doping.…”
Section: Resultsmentioning
confidence: 70%
“…At the same time a strong diamond line is also evident in high pressure grown sheets. These sheets can, therefore, be treated as a composite material; a mixture of sp 2 and sp 3 phase of carbon [22]. As mentioned earlier, the calculation of the value of the proportionality constant A n for different modes of vibrations is quite difficult unless there is an independent technique which can calculate the exact number of H bonded in different modes.…”
Section: Resultsmentioning
confidence: 99%
“…However, accuracy of this method is often seriously limited by the resolution of these C-H bands and ambiguity in assigning them to correct vibrational modes. Moreover, the assumption that all the CH n bands are of uniform absorption cross-section may not hold good if the local surroundings significantly affect the bond strength as indicated by several researchers [24,25]. MacNamara et al [25] proposed to multiply the integrated intensity of an IR band with a constant (A n ) representative of its characteristic oscillator strength in order to find out precise concentration of a particular oscillating species.…”
Section: Resultsmentioning
confidence: 99%